The Role of Cognizant Leadership in Improving Teacher Performance and The Quality of Education at XYZ Elementary School, Jambi - Christian, Gideon; Tung, Khoe Yao (EDULEAD: Journal of Christian Education and Leadership, 2025)
As a developing elementary school, SD XYZ in Jambi operates with a limited budget, which constrains its ability to provide adequate learning facilities, teaching resources, and teacher welfare. This study examines the role of Cognizant Leadership in improving teacher performance and the quality of education at SD XYZ, a new school facing challenges in resource limitations, student retention, and the need for adaptive and reflective leadership. The research employed a single-case qualitative design, with data collected through observation and interviews involving the principal, six teachers, two parents, and representatives of the school foundation. Data analysis followed an inductive process through coding stages of reduction, display, and conclusion drawing. The findings reveal that context-aware leadership has a significant positive impact on teacher motivation and performance, particularly through empathetic, participatory, and empowering approaches. Leadership practices such as openness to feedback, two-way communication, and data-informed evaluation strengthen collaborative and professional school culture. Although Cognizant Leadership has not yet been fully institutionalized, its potential is evident in building trust, improving resource management, and guiding teachers toward higher instructional quality.This study concludes that Cognizant Leadership offers a strategic and contextually relevant approach for developing elementary schools like SD XYZ to become more responsive, reflective, and quality-oriented. The findings contribute to the growing literature on awareness-based leadership and its role in enhancing teacher performance and educational